1998
DOI: 10.1007/s004240050611
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dehydration on apical Na + -H + exchange activity and Na + -dependent sugar transport in brush-border membrane vesicles isolated from chick intestine

Abstract: The current work examines the effect of 4 days of water deprivation on Na+-H+ exchange and Na+-sugar cotransport systems in brush-border membrane vesicles isolated from either the jejunum, ileum or the colon of the chick. Apical Na+-H+ exchange activity was evaluated by measuring the pH-gradient-dependent Na+ uptake. The contribution of the Na+-H+ exchangers NHE2 and NHE3 to total Na+-H+ exchange activity was evaluated from their sensitivity to the amiloride-related drug HOE694. Dehydration increased plasma al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In our previous study (6) we also suggested that AVT regulates jejunal NHE activity because it was not affected by Na ϩ depletion, but it was increased by dehydration. However, the current results show that neither aldosterone nor AVT significantly affected jejunal NHE activity.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…In our previous study (6) we also suggested that AVT regulates jejunal NHE activity because it was not affected by Na ϩ depletion, but it was increased by dehydration. However, the current results show that neither aldosterone nor AVT significantly affected jejunal NHE activity.…”
Section: Discussionmentioning
confidence: 89%
“…As a result, the epithelia of the lower intestine process the ileal and ureteral outflow. We previously reported that dietary Na ϩ depletion decreased Na ϩ -sugar cotransport (SGLT-1) activity and increased that of apical sodium/hydrogen exchange (NHE) in the chick ileum and colon (6,7). We also showed (6) that 4 days of water deprivation increased the activities of both apical NHE and SGLT-1 in jejunum, ileum, and colon of the chicken.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…For example, dehydration results in an increase in sodium-hydrogen exchange, albeit with segmental differences; NHE2 activity increases in the ileum and the colon, while in the jejunum, the activity of both NHE2 and NHE3 increases. Dehydration also leads to an increase in serum aldosterone levels and sodium glucose co-transport in all intestinal segments (De la Horra et al , 1998). Another example of intestinal adaptation is an increase in the intestinal uptake of Ca 2+ and calcium binding protein after restricted feeding during moulting in hens (Berry and Brake, 1991, al-Batshan et al , 1994).…”
Section: Adaptation Of Avian Intestinal Ion Transport To Nutritional mentioning
confidence: 99%
“…ϩ -Glucose Cotransportinduced NHE3 Translocation-Initiation of Na ϩ -glucose cotransport triggers NHE3 translocation to the plasma membrane, thereby activating Na ϩ -H ϩ exchange and resulting in net intestinal Na ϩ absorption (6,7,27,28). Moreover, the net cytosolic alkalinization that results from this NHE3 activation (1) provides the driving force for intestinal H ϩ -dipeptide transport (29).…”
Section: Mapkapk-2 Is Required For Namentioning
confidence: 99%